Audit Quality Moderating Managerial Ownership and ESG Disclosure Effects on Firm Value in Non-Cyclical Consumer Firms - Rauzhatul Husna; Islahuddin; Mulia Saputra (Universitas Muhammadiyah Makassar, 2026)
This study examines the effect of managerial ownership and Environmental, Social, and Governance (ESG) disclosure on firm value, with audit quality as a moderating variable, in consumer non-cyclical firms listed on the Indonesia Stock Exchange during the 2021–2024 period. Grounded in agency theory and signaling theory, this research addresses inconsistencies in prior literature regarding the value relevance of ownership structure and sustainability disclosure in emerging markets. Using a quantitative approach with purposive sampling, 45 firms were selected, resulting in 180 firm-year observations. The data were analyzed using Moderated Regression Analysis (MRA) after passing classical assumption tests. The results reveal that managerial ownership has a significant negative effect on firm value, indicating the presence of managerial entrenchment that outweighs the alignment effect. ESG disclosure is also found to negatively affect firm value, suggesting that investors may perceive sustainability initiatives as short-term cost burdens rather than value-enhancing strategies. Furthermore, audit quality does not moderate the relationship between managerial ownership and firm value, implying limited effectiveness of external monitoring in mitigating ownership-related agency conflicts. However, audit quality significantly strengthens the relationship between ESG disclosure and firm value by enhancing the credibility of sustainability information. This study contributes to the literature by integrating governance, sustainability, and assurance perspectives within a unified framework and provides empirical evidence from an emerging market context, highlighting that the value implications of ESG disclosure depend on information credibility and institutional settings.